Greenhouse Gas Emissions Analysis (Case Study: Construction of a Satpol PP Building) - Wytti, Khalijah Herma; Handayani, Fajar Sri; Setiono, Setiono (Indonesian Journal Publisher, 2024)
The development of the construction world is driven by the demands of meeting various needs, such as in this case study, namely the construction of the Bantul satpol PP Building to meet the needs of the legal apparatus. However, according to the United Nations Environtment Program in the Global Status Report for Buildings and Construction (2021) states that this development has a significant environmental impact, construction projects are responsible for 36% of energy consumption and 37% global CO2 emissions by 2020. Therefore, this research aims of achieving Greenhouse Gas Emission (GHG) efficiency using the Life Cycle Assessment (LCA) method. Data analysis was applied through the Autodesk Revit program to get the material schedule and LCA approach within the scope of Cradle to Gate using ISO 14040 and 14044 guidelines. The structure of foundations, slabs, columns and beams became the object of research because the constituent materials in the form of concrete and steel are considered as CO2 GHG contributors with the largest percentage, reaching 75% of the total emissions released (Luo et al., 2016). The analysis results show that the largest GHG estimate is located in the structural work of the Cradle to Gate scope which reaches 1,657,880.04 KgCO2eq with the most critical process unit which is the material production process unit. Thus, project construction management can look for the best alternatives related to material selection or methods in the material production process that can reduce GHG emissions. This research can be applied to create a sustainable construction.